Study of Coral Reefs in the Tourism Zone of Hoga Island, Wakatobi National Park, Southeast Sulawesi, Indonesia - Hawati, Hawati; Mustafa, Mustafa; Yusuf, Yusuf; Putra, Angkasa; Suriadin, Herianto (Journal La Lifesci, 2024)
One of the ecosystems in tropical waters is the coral reef. Coral reefs serve multiple functions, both ecologically and economically. The marine waters in Wakatobi Regency boast diverse coral reefs, and this study aims to assess the coral reefs in one of its regions, specifically in the waters around Hoga Island, part of Wakatobi National Park. The research was conducted from March to May 2023, involving direct observations at the research site. The collected data were then analyzed and presented descriptively concerning the percentage of coral reefs in the study area. The percentage of coral cover in the growth forms (lifeform) of the Wakatobi National Park tourism zone, region II, revealed that, at the first station, coral cover was 46.33%, dominated by Coral Branching (CB) at 22.36%, and Biotic, primarily Soft Coral (SC), at 14.95%. At the second station, coral cover was 36.13%, with Coral Branching (CB) accounting for 11.53%, and Soft Coral (SC) at 25.33%. The third station exhibited a coral cover percentage of 60.37%.